2010
DOI: 10.1097/bpo.0b013e3181cf118a
|View full text |Cite
|
Sign up to set email alerts
|

Displaced Radial Neck Fractures in Children: Association of the Métaizeau and Böhler Surgical Techniques

Abstract: This is a therapeutic study level IV (case series).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Previous authors have suggested that deformities of 15°to 45°are acceptable 7,13,[25][26][27] , and numerous factors have been variably associated with poor outcomes. Although there are some reports of large series [4][5][6]9,28 , much of the existing literature is limited by modest sample size and restricted to cohort studies of a specific technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested that deformities of 15°to 45°are acceptable 7,13,[25][26][27] , and numerous factors have been variably associated with poor outcomes. Although there are some reports of large series [4][5][6]9,28 , much of the existing literature is limited by modest sample size and restricted to cohort studies of a specific technique.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a substantial amount of malunited fractures, especially those with rotational errors, may have been missed. Some patients with apparently little residual deformity showed poor results 3,5,8 , which might support this assumption.…”
Section: Introductionmentioning
confidence: 81%
“…Radial neck fractures represent 5-10% of all pediatric elbow injuries [1][2][3] . There is common agreement that the treatment algorithm should be based on the initial displacement and angulation deformity of the fracture [4][5][6][7][8] . Most of these fractures may be treated nonoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…1 We appreciate the reinforcement given on the importance of avoiding arthrotomy and specially to the questions brought up to the light of discussion. 1 We appreciate the reinforcement given on the importance of avoiding arthrotomy and specially to the questions brought up to the light of discussion.…”
Section: In Responsementioning
confidence: 98%